Democracy and bioethics - Gracia Guillén, Diego (Acta Bioethica, 2001)
Upon the last 30 years Bioethics has permanently been promoting democratic participation in health care contexts through procedures oriented to decision-making that considers the interests of everyone involved. These procedures imply a continual joined deliberative practice aimed at reaching nuanced and fair solutions. This experience of bioethics allows us to suggest, in a broad sense, the relationship between it and democracy since it has become necessary and urgent to correct democratic deficiencies trying to build it up not only participative but also deliberative.